Respiratory nursing care - Roy Chowdhury, Sunanda S. (New Delhi, India : Jaypee Brothers Medical Publishers (P) Ltd., 2000)
There is a dearth of nursing books written by Indian nurses and which is in accordance with the Indian system of nursing management. This book approach underlines the attempts to adopt this book to the Indian nursing scene. This book has bee designed for students undergoing basic nursing courses though it will also be relevant to nurses undergoing postgraduate course in nursing. This book has adapted a style which will help students to proceed in step-by-step manner in learning about respiratory nursing.
1. Introduction -- 2. Respiratory System: Anatomy -- 3. Respiratory System: Physiology -- 4. Pathophysiology of Respiratory Diseases -- 5. Respiratory Diseases -- 6. Diagnostic Procedures in Respiratory Diseases -- 7. Drugs for Respiratory Diseases -- 8. Special Therapies in Respiratory Diseases -- 9. Surgery in Respiratory Diseases -- 10. Nursing Management of the Respiratory Problems -- 11. Intensive Respiratory Care Unit (IRCU) -- 12. In-service Education on Intermittent Positive Pressure Breathing (IPPB) -- 13. Respiratory Nursing Research -- Glossary -- Index.
Includes index.
Keywords: RESPIRATORY -- TRACT -- DISEASES NURSING